2013
DOI: 10.1103/physrevlett.110.145701
|View full text |Cite
|
Sign up to set email alerts
|

Inherent Structure Landscape Connection between Liquids, Granular Materials, and the Jamming Phase Diagram

Abstract: We provide a comprehensive picture of the jamming phase diagram by connecting the athermal, granular ensemble of jammed states and the equilibrium fluid through the inherent structure paradigm for a system of hard disks confined to a narrow channel. The J line is shown to be divided into packings that are either accessible or inaccessible from the equilibrium fluid. The J point itself is found to occur at the transition between these two sets of packings and is located at the maximum of the inherent structure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 51 publications
1
40
0
Order By: Relevance
“…Clearly, we see that there is rich behavior to be found amidst the rattlerbackbone interactions in disordered, jammed sphere packings, highlighting the need for a statistical mechanical theory that is capable of accounting for such behavior. Moreover, understanding rattler phenomena in confined geometries [47] represents another fascinating area for future research.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Clearly, we see that there is rich behavior to be found amidst the rattlerbackbone interactions in disordered, jammed sphere packings, highlighting the need for a statistical mechanical theory that is capable of accounting for such behavior. Moreover, understanding rattler phenomena in confined geometries [47] represents another fascinating area for future research.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It has been frequently observed that disks moving in a narrow channel can provide useful insights into glassy behavior [1][2][3][4][5][6][7]. In a recent paper [6] two of us studied the static and dynamic properties of N disks of diameter σ, which move in a narrow channel consisting of two impenetrable walls (lines) spaced by a distance H d , such that 1 < H d /σ < 1 + √ 3/2 (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This number is readily determined in numerical work using the procedure given in Ref. [3]. Figure 11 shows θ as a function of packing fraction φ obtained from the simulations and compared with the analytical approach of Ref.…”
mentioning
confidence: 99%
“…In the NN model, the dynamics becomes activated around a packing fraction φ d > 0.48 [1][2][3][4][5]. This is due to the onset of caging, a feature connected with the growth of a particular structural feature, zigzag order [1,2].…”
Section: Introductionmentioning
confidence: 99%